2022
DOI: 10.1007/s13760-022-02141-6
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Parkinson’s disease: a systematic review and meta-analysis

Abstract: This meta-analysis aimed to determine the prevalence, symptoms, and outcomes of COVID-19 in the elderly with Parkinson’s disease (PD) by searching in the international databases of PubMed, Scopus, Web of Sciences, and EMBASE using the keywords of “COVID-19” and “Parkinson’s.” All articles related to Parkinson's disease and COVID-19 from January 2019 to October 20, 2021 were reviewed. The STATA software was used for analysis. A total of 20 articles were selected for data extraction in this meta-analysis, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…It can occur at every stage of PD, often persist, and may worsen over time. A meta‐analysis showed that the symptom of fatigue due to COVID‐19 was 1.20 times greater in patients with PD than ones without PD (Afraie et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…It can occur at every stage of PD, often persist, and may worsen over time. A meta‐analysis showed that the symptom of fatigue due to COVID‐19 was 1.20 times greater in patients with PD than ones without PD (Afraie et al., 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has impacted healthcare delivery, and this alone has adversely affected the care delivered to PD patients [ 17 , 27 , 28 ]. Isolation, altered medical supply, and poor access to healthcare adversely affect the QOL in PD patients.…”
Section: Discussionmentioning
confidence: 99%
“…No study has correlated Ramadan fasting to QOL. In addition, the COVID-19 pandemic has impacted many patients with PD in different aspects [ 16 , 17 ]. This study aimed first to assess the level of QOL in patients with PD, second to evaluate the relationship between the factors (i.e., determinants of fasting for Ramadan and COVID-19) influencing QOL in patients with PD, and lastly to determine the association between sociodemographic factors and QOL in patients with PD.…”
Section: Introductionmentioning
confidence: 99%
“…Five systematic reviews assessed the impact of PD on COVID-19 severity across 279,934 patients with PD ( Table 5 ) [ [29] , [30] , [31] , [32] , [33] ]. Across several of these reviews it was found that the risk of severe COVID-19 in PD patients increased with age [ [29] , [30] , [31] ].…”
Section: Disease-specific Relationships To Covid-19 Severitymentioning
confidence: 99%
“…Additionally, PD was associated with poor in-hospital outcomes, increased infection severity, and increased risk of mortality in a majority of the reviews. However, one meta-analysis with a large sample size of 75,701 cases did not find a significant correlation between history of PD and COVID-19 hospitalization and mortality rates compared to the general population [ 33 ].…”
Section: Disease-specific Relationships To Covid-19 Severitymentioning
confidence: 99%